STUDI KASUS PESERTA DIDIK SULIT MENGENDALIKAN EMOSI MARAH KELAS X SMA ISLAM BAWARI PONTIANAK - Nur Indah Sari; Yuline Yuline; Purwanti Purwanti (Universitas Tanjungpura, 2019)
AbstractThe study that was carried out in this study was grade X students of SMA Islam Bawari Pontianak who had difficulty controlling their anger. The general problem in this study is how to help students who are difficult to control angry emotions in class X Bawari Islamic High School Pontianak. While the aim is to obtain the appropriate causative factors and alternative assistance to be used in overcoming students' problems that are difficult to control angry emotions in class X Bawari Islamic High School Pontianak. The approach used in this research is qualitative by using descriptive methods and the form of research is case studies. Data collection techniques used were non-test techniques using data collection tools such as interview guides, observation guides, home visits and documentation. Alternative assistance given to case 1 subjects is using Behavioral counseling models with shaping techniques, while case II subjects use RET (Rational Emotive Therapy) counseling models. Keywords: Case Study, Difficult to Control Anger Emotions